Calcium Titanate from Food Waste: Combustion Synthesis, Sintering, Characterization, and Properties - Siriluk Cherdchom; Thitiwat Rattanaphan; Tawat Chanadee (Advances in Materials Science and Engineering)
Calcium titanate (CaTiO3) was combustion synthesized from a calcium source of waste duck eggshell, anatase titanium dioxide (A-TiO2), and magnesium (Mg). The eggshell and A-TiO2 were milled for 30 min in either a high-energy planetary mill or a conventional ball mill. These powders were then separately mixed with Mg in a ball mill. After synthesis, the combustion products were leached and then sintered to produce CaTiO3 ceramic. Analytical characterization of the as-leached combustion products revealed that the product of the combustion synthesis of duck eggshell + A-TiO2 that had been high-energy-milled for 30 min before synthesis comprised a single perovskite phase of CaTiO3. The high-energy milling of the reactant powder had generated a large reactive surface area and induced structural defects, both of which drove the completion of the combustion reaction and the phase conversion of the reactants into the product. A calcium titanate ceramic, fabricated by sintering as-leached powdered combustion product at 1350°C for 180 min, achieved a maximum density of 3.65 g/cm3 and a minimum porosity of 0.54%. The same fabricated calcium titanate ceramic product also exhibited the highest dielectric constant (∼78) and the lowest dielectric loss (∼0.02), which resulted from the simplified charge polarization process.